(untitled) (Journal of Hama University, 2019)
A large number of existing concrete structures in Syria have suffered from problems of deterioration destruction and partial destruction, resulting in a reduction in the life span or operational life. As funding sources are generally unavailable to replace degraded facilities with new facilities, maintenance, preventive reinforcement, and corrective measures to extend useful life in a cost-effective manner. Measures to extend the operational life of the concrete elements depend on whether the purpose of the protection is to control the damage caused by the destruction, or to increase the structural efficiency of the installations, or both at the same time. Since the data on the performance of the installations after the reform during the design age, in addition to information on the supposed extension of the design age needs to be evaluated in advance before the necessary reinforcement of the structural component. Modern and important things are the repair and reinforcement of the structural elements, Due to the remarkable progress in the materials used in the consolidation process, the many types, and differences, and the large increase in the prices of building materials, many countries have become dependent on repairing structural elements, and self-reliance on the production of these materials to repair defects In the old installations, or installations affected by earthquakes or external factors, such as shocks and explosions. so must be aware of this modern science and good study and interest in the discovery of materials to implement the process of consolidation and reform in the future.